Tracking photo‐degradation of triarylmethane dyes with surface‐enhanced Raman spectroscopy. (25th October 2016) - Cesaratto, Anna; Lombardi, John R.; Leona, Marco
Abstract : The triarylmethane dyes, basic fuchsine, methyl violet, and crystal violet, were some of the first synthetic colorants to be produced after the revolutionary invention of mauve in 1856. While their attractive pink‐to‐violet hues made them immediately interesting to the textile industry and the arts, they are prone to fade when exposed to light. This work aims to investigate basic fuchsine, methyl violet, and crystal violet and their degradation products through surface‐enhanced Raman spectroscopy (SERS), exploiting the high sensitivity and minimal sample requirement of the technique. SERS is not able to discriminate between the two less methylated basic fuchsine homologues, rosaniline and pararosaniline, and between crystal and methyl violet, but it does distinguish rosaniline/pararosaniline from new fuchsine, the highest methylated basic fuchsine homologue, and those from crystal/methyl violet. Furthermore, we demonstrate that SERS is a valuable tool to study the photo‐induced N‐demethylation by tracking spectral changes in a series of artificially aged samples. The new findings have been applied to the analysis of a group of late 19th century woodblock Japanese prints. This approach shows a great potential in both forensic and conservation science fields, especially when the minimum sample availability and the low concentration of the colorants in the sample prevent the application of other better established techniques, such as high performance liquid chromatography with diode array, fluorescence, or mass spectrometric detections. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This work aims to study the photo‐degradation products of triarylmethane dyes by Surface‐Enhanced Raman Spectroscopy (SERS). After comparing the SERS spectra of basic fuchsine, methyl violet, and crystal violet, the feasibility of SERS to evaluate the N‐demethylation degradation process of crystal violet have been verified. The results have been used to interpret the data obtained from Meiji Japanese woodblock prints.